The Arboreal Empire and the 'Parliament of Things': Australian Trees in Colonial South India. (1st March 2020) - Arnold, David
In the second half of the nineteenth century India and Australia were linked through a series of ecological exchanges, among the most important of which was the introduction of such Australian trees as eucalyptus, casuarina and acacia. South India was particularly affected by these importations, especially the Nilgiri hills, a plausible 'neo-Europe'. But, contrary to A. W. Crosby's argument about 'ecological imperialism', many of these introductions relied heavily on calculated human agency and transoceanic networks of foresters and horticulturalists for their success; other attempted transfers either failed or took off in unpredictable ways. The motives behind the introduction of Australian tree species varied but included the acute shortage of fuelwood in south India, colonial landscape aesthetics, an ideology of 'improvement' and belief in the transferability of species within the same temperate or tropical climatic zone. By 1914 experience had revealed the complexity of these ecological exchanges and their limitations, as well as the ability of some introduced species to become 'wild' and 'invasive'.